Positive Energy District (PED) Selected Projects Assessment, Study towards the Development of Further PEDs - Rueda Castellanos Sofia (Sciendo, 2021)
Positive Energy District (PED) is a relatively new concept from which many projects are planned, however, only a few cases are currently close to be materialized, therefore, in this study the PED projects in operation and in implementation process in existing districts are gathered in order to serve as a base for future PEDs. In this sense, certain points of each selected project are highlighted due to their relevance within the project development and their replicability potential. Furthermore, intending to learn from the experience of the assessed case-studies, this paper aims to understand the current situation regarding PED implementation to simplify the development of further PEDs.